Long non-coding RNA LINC00926 regulates WNT10B signaling pathway thereby altering inflammatory gene expression in PTSD - Marpe Bam; Xiaoming Yang; Jay P. Ginsberg; Allison E. Aiello; Monica Uddin; Sandro Galea; Prakash S. Nagarkatti; Mitzi Nagarkatti (Translational Psychiatry, 2022)
Abstract Post-traumatic stress disorder (PTSD), which frequently occurs in the aftermath of a psychologically traumatic event is characterized by heightened inflammation. People with PTSD also suffer from a number of comorbid clinical and behavioral disorders that are related to chronic inflammation. Thus, understanding the mechanisms of enhanced inflammation in PTSD can provide insights into the relationship between PTSD and associated comorbid disorders. In the current study, we investigated the role of large intervening non-coding RNAs (lincRNAs) in the regulation of inflammation in people diagnosed with PTSD. We observed that WNT ligand, WNT10B, was upregulated in the peripheral blood mononuclear cells (PBMCs) of PTSD patients. This observation was associated with higher H3K4me3 signals around WNT10B promotor in PTSD patients compared to those without PTSD. Increased H3K4me3 resulted from LINC00926, which we found to be upregulated in the PTSD sample, bringing in histone methyltransferase, MLL1, onto WNT10B promotor leading to the introduction of H3K4 trimethylation. The addition of recombinant human WNT10B to pre-activated peripheral blood mononuclear cells (PBMCs) led to increased expression of inflammatory genes such as IFNG and IL17A, suggesting that WNT10B is involved in their upregulation. Together, our data suggested that LINC00926 interacts physically with MLL1 and thereby controls the expression of IFNG and IL17A. This is the first time a long non-coding RNA is shown to regulate the expression of WNT10B and consequently inflammation. This observation has high relevance to our understanding of disease mechanisms of PTSD and comorbidities associated with PTSD.